Application of Modeling Technique to Improve Learning Interest of Slow Learner Students in Elementary School - Andini Salsabilla Putri; Prianggi Amelasasih (Universitas Negeri Medan, 2025)
Low learning interest is one of the main problems commonly experienced by slow learner students in elementary schools. This condition affects students’ attention, participation, and willingness to engage in learning activities. Therefore, learning strategies that provide concrete and easily understood learning experiences are needed for slow learner students. This study aims to describe the implementation of the modelling technique in improving the learning interest of slow learner students in elementary school. This research employed a qualitative approach with a one-group pre-test–post-test design. The research subjects consisted of three third-grade students categorized as slow learners. Data were collected through observation, interviews, and documentation. Learning interest was measured based on three aspects: attention, enjoyment, and enthusiasm. The results showed that the application of the modelling technique led to positive changes in students’ learning interest, indicated by increased attention during learning, more active participation in classroom activities, and improved self-confidence. Statistical analysis using the Wilcoxon Signed-Rank Test showed a significance value of p = 0.102, indicating that the improvement was not statistically significant. However, the consistent positive behavioral changes observed in all subjects suggest that the modelling technique has a positive practical impact on improving the learning interest of slow learner students. Thus, the modelling technique can be considered an alternative adaptive learning strategy to support inclusive learning in elementary schools.